Species and Characteristics of the Sansevera Plant - Rizayev Farrux Farxod o'g'li; Ochilov Tulkin Ashurovich; Axmadjonova Nozanin; Usmanova Shakhnoza Anvarovna; Raximova Umida Baxriddin qizi (International Journal on Orange Technologies, 2022)
The types of Sansevera plants were analyzed, and research was conducted on which type of fiber can be obtained from them. The results of the study showed that only one type of fiber can be obtained.